2008
DOI: 10.1097/dad.0b013e31815b9c82
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Metaplastic Synovial Cyst in Ehlers-Danlos Syndrome: Report of a Second Case

Abstract: A cutaneous metaplastic synovial cyst is a rare entity that is probably caused by trauma or surgery. We report the second case of cutaneous metaplastic synovial cyst in a child with Ehlers-Danlos syndrome. His father is also affected with Ehlers-Danlos syndrome, and his diagnosis is substantiated by the demonstration of reduced synthesis of collagen type V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
(4 reference statements)
0
8
0
Order By: Relevance
“…These cells are difficult to be distinguished by those, such as dermatologists, who are unfamiliar with synovial tissue. Positive immunoreactivity of lining cells against vimentin, but not against cytokeratin, CEA, or S-100, 3 together with the absence of expression of synovium marker CD68, supports the diagnosis.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…These cells are difficult to be distinguished by those, such as dermatologists, who are unfamiliar with synovial tissue. Positive immunoreactivity of lining cells against vimentin, but not against cytokeratin, CEA, or S-100, 3 together with the absence of expression of synovium marker CD68, supports the diagnosis.…”
Section: Discussionmentioning
confidence: 67%
“…2 CMSC usually appears at the site of previous surgery or trauma and is not related to joint or synovial structures. 3 CMSC is not considered to be a true cyst because it lacks a definite epithelial lining. 1 Synovial cysts have been predominantly discussed in the field of orthopedic medicine or pathology.…”
Section: Introductionmentioning
confidence: 99%
“…Since first described in 1987 by Gonzalez et al1, 23 cases of CMSC have been reported in 12 English language studies1-12. The current CMSC case was rare as it was on the sole without a history of previous trauma or surgical procedure.…”
Section: Discussionmentioning
confidence: 86%
“…Although the exact cause of CMSC has remained unclear, 13 of 23 reported cases have had histories of local trauma. Further, three of ten cases that have occurred spontaneously without local trauma were accompanied by Ehlers-Danlos syndrome3,10,12, which led us to believe that abnormal healing after microtrauma was a pathogenic mechanism of CMSC. Additionally, the fact that four cases of CMSC have accompanied rheumatoid arthritis6,9 and arthrosis10 suggested that chronic inflammation, constant pressure, and repeated manipulation have played critical roles in the pathogenesis of the lesions.…”
Section: Discussionmentioning
confidence: 99%
“…This lesion was reported in a wide age range (7 to 82 years), but most patients were older than 40 years old ( Table 1 ). In two reports, the reported lesions in a 7 and a 15 year-old patient were assumed to be a manifestation of Ehlers-Danlos Syndrome ( 12 , 13 ). Although our patient was young, no signs of Ehlers-Danlos syndrome and related manifestations were found.…”
Section: Discussionmentioning
confidence: 99%